Anatomical and behavioral characterization of three hemiplegic animal models - Mei Liu; Lingling Xu; Gefei Cheng; Yang Yang; Likun Yang; Yuhai Wang (BMC Neuroscience)
Abstract Background Hemiplegia is characterized by muscle weakness on one side of the body, often resulting from damage to the brain, spinal cord, or associated nerves. This condition commonly occurs due to strokes, traumatic brain injuries (TBI), or spinal cord injuries (SCI), which can damage corticospinal neurons (CSNs) and the corticospinal tract (CST). However, there is still a notable lack of comprehensive studies that systematically characterize the anatomical and behavioral aspects of these hemiplegic animal models. Objective This study aimed to validate and compare existing models of TBI, stroke, and SCI in order to identify the most suitable preclinical hemiplegia models for future research. Method Using viral-based retrograde tracing, we first mapped the cortical distribution of CSNs responsible for hindlimb movement. Anterograde and retrograde viral tracing techniques were then employed to label and evaluate the damage to CSNs and the CST in three models: photothrombotic stroke, Feeney’s weight-drop TBI, and T10 hemi-section SCI. We also conducted behavioral tests to assess spontaneous motor function recovery, including open field and rotarod tests for gross motor function, as well as beam walking and irregular ladder walking tasks for assessing skilled motor function. Results Our findings revealed that the CSNs controlling hindlimb movement are concentrated in the hindlimb region of the primary somatosensory cortex (S1HL). In the TBI and stroke models, there was complete destruction of ipsilateral CSNs in the S1HL and loss of CST fibers governing hindlimb movement. In the SCI model, ipsilateral CST fibers below T10 were also lost. After 8 weeks post-injury, all three groups of hemiplegic mice showed improvements in motor function, with gross motor function returning to normal levels; however, the recovery of skilled motor function was only modest. Notably, the degree of improvement in fine motor skills varied among the hemiplegia models, with mice subjected to brain injury (stroke and TBI) demonstrating significantly greater recovery in fine motor skills compared to those with SCI. Conclusion We confirmed and validated previous hemiplegia models by damaging CSNs or CST controlling hindlimb movement. Post-injury, gross motor function gradually returned to normal levels across all groups, whereas recovery of skilled motor function was limited. Furthermore, there were significant differences in the recovery of skilled motor function between brain injury models and the SCI model. These hemiplegic mouse models are valuable tools for studying post-injury skilled motor functions. Clinical trial number Not applicable.